Bioimpedancespectroscopy Detecting Overhydrationis Associated with Systolic Blood Pressure in Asian Chronic Kidney Disease Patients. (June 2015) - Ho, Peh Joo; Wong, Tien Yin; CharumathiSabanayagam,; Lee, Evan J.C.; Teo, Boon Wee
Abstract : Introduction: Bioimpedance spectroscopy measures overhydration (OH), which is used to manage hypertension in non-Asian dialysis patients. OH is calculated from equations derived from populations including chronic kidney disease (CKD) patients on dialysis. It is unclear if this applies to managing hypertension in Asian patients. Objective: We examined the cross-sectional association of OH with systolic (SBP) and diastolic (DBP) blood pressures in a population of Asianpredialysis CKD and dialysis patients. Methods: We prospectively recruited 352 patients (59.4% male, Chinese 65.3%, mean age 61.8 ± 10.7 years, 46 on dialysis; 52%, 84.4%, and 25.9% with previously diagnosed diabetes, hypertension, and coronary artery disease, respectively). They underwent bioimpedance spectroscopy with the Fresenius Body Composition Monitor (BCM). Standard statistical tests and linear regression were used to correlate SBPand DBP (mmHg) with OH. Results: Overall, averageSBP was 140 ± 22, DBP was 74 ± 11, and median OH was 1.0L (IQR: 0.2–2.0). Non-dialysis CKD patients had mean SBP of 139 ± 20, DBP74 ± 11, and median OH of 1.0L (IQR: 0.1–1.9). By linear regression, SBP was associated with OH, SBP = 137.8 + 1.39 × OH ( p  = 0.0496); but DBP was not associated with OH. Patients on dialysis had mean SBP of 146 ± 30, DBP 76 ± 13, and median OH of 1.6L (IQR: 0.35–2.6). By linear regression, SBP was associated with OH, SBP = 130.3 + 8.8 × OH ( p  < 0.001); but DBP was not associated with OH. Conclusions: The Fresenius BCM overhydration indicator is associated with SBP in Asian predialysis CKD and dialysis patients, and may be useful in guiding antihypertensive therapy in Asians.